Methodology of the Experiments to Study Lithium CPS Interaction with Deuterium Under Conditions Of Reactor Irradiation - Samarkhanov, Kuanysh; Ponkratov, Yuriy; Nikitenkov, Nikolay; Tazhibayeva, Irina; Zaurbekova, Zhanna; Gnyrya, Vyacheslav; Lyublinski, Igor; Mazzitelli, Giuseppe (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems. Institute of Batteries LLP, Nazarbayev University, and PI “National Laboratory Astana”., 2018)
Problems of plasma-facing materials degradation and in-vessel element destructions, tritium accumulation and plasma pollution can be overcome by the use of liquid metals with low atomic number. The best candidate as a material for divertor receiving plates and other in-vessel devices is lithium. Liquid lithium advantages as a plasma facing material have been confirmed by a large number of the experiments at the plasma-physical facilities being operated worldwide.
Keywords: Lithium; plasma-facing materials; capillary-porous systems (CPS)